2015
DOI: 10.1371/journal.ppat.1005101
|View full text |Cite
|
Sign up to set email alerts
|

Mucosal B Cells Are Associated with Delayed SIV Acquisition in Vaccinated Female but Not Male Rhesus Macaques Following SIVmac251 Rectal Challenge

Abstract: Many viral infections, including HIV, exhibit sex-based pathogenic differences. However, few studies have examined vaccine-related sex differences. We compared immunogenicity and protective efficacy of monomeric SIV gp120 with oligomeric SIV gp140 in a pre-clinical rhesus macaque study and explored a subsequent sex bias in vaccine outcome. Each immunization group (16 females, 8 males) was primed twice mucosally with replication-competent Ad-recombinants encoding SIVsmH4 env/rev, SIV239 gag and SIV239 nefΔ1–13 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
79
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(96 citation statements)
references
References 79 publications
14
79
2
Order By: Relevance
“…Vaccine approaches in many of these studies included priming with plasmid DNA encoding SIV/HIV immunogens followed by the administration of viral vectors (modified vaccinia virus Ankara, adenovirus type 5) (31,32,50) or priming with viral vectors followed by recombinant protein boosts (39,(51)(52)(53)(54)(55). Consistent with the findings of these studies, analysis of correlates of protection in our current study revealed that the magnitude of the Env-specific binding antibody titers at week 37 prechallenge correlated strongly with the protection induced by immunization with protein-NP (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Vaccine approaches in many of these studies included priming with plasmid DNA encoding SIV/HIV immunogens followed by the administration of viral vectors (modified vaccinia virus Ankara, adenovirus type 5) (31,32,50) or priming with viral vectors followed by recombinant protein boosts (39,(51)(52)(53)(54)(55). Consistent with the findings of these studies, analysis of correlates of protection in our current study revealed that the magnitude of the Env-specific binding antibody titers at week 37 prechallenge correlated strongly with the protection induced by immunization with protein-NP (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…ADCP was measured by a modified form of a previously described method (23). Biotinylated gp120 (5 g) was incubated with 1 l streptavidin-fluorescent beads (FluoSpheres NeutrAvidin-labeled microspheres, 1.0 m, yellow-green fluorescent [505/515 nm], 1% solids; Invitrogen) that were diluted 100-fold for 25 min at room temperature in the dark.…”
Section: Construction Of Linear Ig Expression Cassettesmentioning
confidence: 99%
“…Locally produced or passively administered mucosal IgA antibodies can block entry and spread of experimental SIV/SHIV infection as shown in various nonhuman primate models (38)(39)(40). The finding that oral PrEP use is associated with elevated mucosal HIV-1-neutralizing IgA responses warrants further study in humans and nonhuman primate models to elucidate whether induced mucosal immune responses could augment oral PrEP efficacy and overall protection from HIV-1 acquisition.…”
Section: Discussionmentioning
confidence: 94%